Design and Numerical Study of Semiconductor Nanolaser With Gaussian-Shaped Metallic Cavity - Baifu Zhang; Kang Zhu; Jingjing Hao; Bowen Wang; Zhe Shen; Haifeng Hu (IEEE Photonics Journal, 2018)
We propose and numerically investigate a novel metallic semiconductor nanolaser for 1.55-μm wavelength range with Gaussian-shaped cavity structure. By introducing cylindrical facets and curved sidewalls, Gaussian-like resonant mode can be tightly confined in the center of the cavity with reduced electric field component perpendicular to the metallic sidewalls, yielding to significant reduction of plasmonic loss and improvement of Q factor and confinement factor. Three-dimensional finite-difference time-domain simulations are conducted and demonstrate the effectiveness of the proposed nanolaser structure. As an example case with subwavelength cavity volume of 0.27λ 3, the proposed structure can improve Q factor and confinement factor from 108 and 0.298 of conventional rectangular cavity to 164 and 0.539, respectively, resulting in a dramatic reduction of threshold current from 577 mA to 165 μA. In addition, the dependence of nanolaser properties on cavity geometry is also numerically investigated in this paper.